"TO PUT THE CAMERA BACK IN THE HANDS OF HONEST PHOTOGRAPHERS": The activist pedagogy of the photo league. (2nd January 2019) - Gil-Glazer, Ya'ara
Abstract : Founded during the Depression and disbanded during the post-war prosperity and McCarthy's redbaiting, the New York Photo League was a radical hub for photographers both professional and amateur. This article focuses on the unique pedagogy of its school, particularly of its leading teacher Sid Grossman. It contributes to our understanding of the relatively understudied role of pedagogic thinking in the history of the medium in the US. More specifically, the League's school is discussed here as a unique and ground-breaking historical example of social-documentary oriented activist pedagogy. This is done by examining the sources of photographic knowledge its teachers conveyed to its students; its educational approach to documentary photographic practice; and the social-aesthetic discourse developed and promoted by its teachers, including the conflict of views within the League as represented by two prominent documentary projects: Grossman's Chelsea Document and Aaron Siskind's Harlem Document. The conclusion refers critically to the League's acceptance in recent years in the context of its growing commodification. This prevalent retrospective view of the League downplays its school's distinctive activist education and Grossman's radical pedagogic legacy.